MODEL PENDIDIKAN KARAKTER MELALUI PENDIDIKAN AGAMA: KASUS DI SMAN 3 MEDAN: MODEL OF CHARACTER EDUCATION THROUGH THE RELIGIOUS EDUCATION: THE CASE OF SENIOR HIGH SCHOOL (SMAN) 3 MEDAN - Imran Siregar (Penamas, 2015)
This paper presents the results of research on the model of organization of character education in school, with the case of Public Senior High School (SMAN) 3 Medan. This study used a qualitative approach by conducting in- depth interviews to key informants, such as principal, teachers of religious education, the student’s parents and the Students Executive Board (OSIS) as wekk as equipped with observation or analysis of documents. This study findings that character education applied in SMAN 3 is an integrative model, involving all components of the school and teachers of religious education becomes the main actor (model) with conducive policy support from the principal. Presence and involment of campus activists through mentoring requires attention and coordination with integrated program of teachers of religious education. Keywords: Character education, religious education, Senior High School, Medan Tulisan ini menyajikan hasil penelitian tentang model penyelenggaraan pendidikan karakter di sekolah, dengan kasus di SMAN 3 Medan. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan wawancara mendalam kepada informan kunci, seperti kepala sekolah, guru pendidikan agama, pengurus OSIS, dan orangtua siswa serta dilengkapi dengan pengamatan maupun analisis dokumen. Temuannya antara lain, bahwa pendidikan karakter yang diterapkan di lingkungan SMAN 3 Medan adalah model integratif yang melibatkan seluruh komponen sekolah dan guru pendidikan agama menjadi aktor utamanya (model) dengan dukungan kebijakan yang kondusif dari kepala sekolah. Kehadiran dan keterlibatan aktivis kampus melalui mentoring memerlukan pencermatan dan koordinasi yang terintegrasi dengan program guru pendidikan agama. Kata Kunci: Pendidikan karakter, pendidikan agama, model pendidikan, SMA